Thermal plasticity in the invasive south American tomato pinworm Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae) - Tarusikirwa, Vimbai L.; Mutamiswa, Reyard; English, Sinead; Chidawanyika, Frank; Nyamukondiwa, Casper (Elsevier, 2022)
South American tomato pinworm, Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae) is a devastating invasive global insect pest of tomato, Solanum lycopersicum (Solanaceae). In nature, pests face multiple overlapping environmental stressors, which may significantly influence survival. To cope with rapidly changing environments, insects often employ a suite of mechanisms at both acute and chronic time-scales, thereby improving fitness at sub-optimal thermal environments. For T. absoluta, physiological responses to transient thermal variability remain under explored. Moreso, environmental effects and physiological responses may differ across insect life stages and this can have implications for population dynamics. Against this background, we investigated short and long term plastic responses to temperature of T. absoluta larvae (4th instar) and adults (24–48 h old) from field populations. We measured traits of temperature tolerance vis critical thermal limits [critical thermal minima (CTmin) and maxima (CTmax)], heat knockdown time (HKDT), chill coma recovery time (CCRT) and supercooling points (SCP). Our results showed that at the larval stage, Rapid Cold Hardening (RCH) significantly improved CTmin and HKDT but impaired SCP and CCRT. Heat hardening in larvae impaired CTmin, CCRT, SCP, CTmax but not HKDT. In adults, both heat and cold hardening generally impaired CTmin and CTmax, but had no effects on HKDT, SCP and CCRT. Low temperature acclimation significantly improved CTmin and HKDT while marginally compromising CCRT and CTmax, whereas high temperature acclimation had no significant effects on any traits except for HKDT in larvae. Similarly, low and high temperature acclimation had no effects on CTmin, SCPs and CTmax, while high temperature acclimation significantly compromised adult CCRT. Our results show that larvae are more thermally plastic than adults and can shift their thermal tolerance in short and long timescales. The larval plasticity reported here could be advantageous in new environments, suggesting an asymmetrical ecological role of larva relative to adults in facilitating T. absoluta invasion.